MLK4 as an immune marker and its correlation with immune infiltration in Cervical squamous cell carcinoma and endocervical adenocarcinoma(CESC). - Meng Gong; Fujin Shen; Yang Li; Lei Ming; Li Hong (PLoS ONE, 2023)
Mixed pedigree kinase 4 (MLK4) is a member of the serine/threonine kinases mixed pedigree kinase (MLKs) family. Few reports on immune-related targets in Cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), and the role of MLK4 in cervical cancer remains to be studied. The expression of MLK4 in CESC was analyzed by TCGA database containing 306 CESC tissues and 3 peritumoral tissue samples, and the effect of MLK4 on immune invasion was evaluated using the Deseq2 package(Benjamini-Hochberg corrected p-value < 0.05 and log2 fold change ≥|2|). Tissue microarray was used to verify the expression of MLK4 in CESC patients, and it was found that MLK4 was significantly overexpressed in CESC, and significantly correlated with WHO grade. Multiple analysis algorithms revealed that the high expression of MLK4 was negatively correlated with immune cell infiltration in CESC. Analysis showed that MLK4 expression was negatively correlated with the infiltration of various immune cells including CD8+T cells, and MLK4 mRNA expression was positively correlated with immune checkpoints PD-L1,CTLA4, LAG3, and negatively correlated with immune promotion genes CD86 and CD80. Furthermore, vitro assays were performed to investigate the biological characteristics of MLK4 in C33A cells. The EDU and transwell assays demonstrated that the decrease in MLK4 expression in C33A cells resulted in a decrease in cell proliferation and invasion. The silencing of MLK4 resulted in a significant increase in the expression of inflammatory cytokines IL-1β(p<0.05), TNF-α(p<0.01), and IL-6 (p<0.05). The results of cell assays indicate that knocking down MLK4 would inhibit the expression of established biochemical markers CEA, AFP and HCG. Hence, it is plausible that MLK4 could potentially exert a significant influence on the development and progression of Cervical cancer.